1997
DOI: 10.1016/s0736-5748(97)00029-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine regulation of embryonic rat dopamine and serotonin neuronal survival in vitro

Abstract: Interleukin-1beta (IL-1beta), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-alpha) are cytokines with pleiotropic effects in the central nervous system (CNS), including an emerging role in neurodevelopment. This study measured the effects of cytokines on the survival of tyrosine hydroxylase (TH) immunoreactive dopamine neurons from the substantia nigra (SN), and 5-hydroxytryptamine (5-HT) immunoreactive serotonin neurons from the rostral raphe (RR), using cultures from embryonic day 14 (E14) rat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 16 publications
0
84
1
Order By: Relevance
“…(a) The administration of systemic AMPH (2.5 mg/kg, intraperitoneally) led to a general increase in locomotor activity, with offspring of PolyI:C-treated mothers displaying a potentiated locomotor response to the drug treatment independent of the genetic background. ANOVA of distance traveled in response to AMPH treatment yielded a significant prenatal treatment  bins interaction term (F (11,330) = 2.39; P < 0.01). Subsequent ANOVAs restricted to each of the 5-min bins further showed that prenatal PolyI:C exposure significantly enhanced the locomotor reaction to AMPH between 5 and 30 min post-injection in comparison with prenatal vehicle treatment (*P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(a) The administration of systemic AMPH (2.5 mg/kg, intraperitoneally) led to a general increase in locomotor activity, with offspring of PolyI:C-treated mothers displaying a potentiated locomotor response to the drug treatment independent of the genetic background. ANOVA of distance traveled in response to AMPH treatment yielded a significant prenatal treatment  bins interaction term (F (11,330) = 2.39; P < 0.01). Subsequent ANOVAs restricted to each of the 5-min bins further showed that prenatal PolyI:C exposure significantly enhanced the locomotor reaction to AMPH between 5 and 30 min post-injection in comparison with prenatal vehicle treatment (*P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, the macrophage-specific overexpression of IL-10 also abolished the fetal brain TNF-a response to maternal immunological stimulation. TNF-a is known to have potent neurodevelopmental effects by inhibiting neuronal cell survival 11 and cortical dendrite development 12 and synergistic interactions exist between TNF-a and other proinflammatory cytokines in these processes. 12,39 Elevated fetal brain levels of TNF-a have also been implicated in the emergence of enhanced neuronal apoptosis in postnatal life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, experimentation in animals has confirmed that, in the absence of a specific pathogen, prenatal exposure to cytokine-releasing agents (Shi et al, 2003;Zuckerman et al, 2003;Zuckerman and Weiner, 2005;Meyer et al, 2005Meyer et al, , 2006aOzawa et al, 2006) is sufficient to induce psychopathology in later life. Third, in addition to their immunological roles (Curfs et al, 1997), pro-inflammatory cytokines have various neurodevelopmental effects (eg Ling et al, 1998;Jarskog et al, 1997;Gilmore et al, 2004). Hence, an imbalance in pro-inflammatory cytokine may trigger mal-neurodevelopment in the developing fetus and ultimately precipitate neuropathology and psychopathology in the adult offspring.…”
Section: Introductionmentioning
confidence: 99%